دور نظم المعلومات الإدارية في جودة القرارات الإدارية - محمدأ. علي إدريس; مسعود أ. محمد سليمان; الهماليد. الهمالي صالح (Aljameai, 2022)
الملخص: هدفت الدراسة إلى التعرف على دور نظم المعلومات الإدارية في جودة القرارات الإدارية فى المعاهد العليا العامة بمدينة اجدابيا، حيث استخدم المنهج الوصفي التحليلي، واستخدام الاستمارة كأداة لجمع البيانات، كما استخدام أسلوب المسح الشامل للمجتمع، وكان عدد الاستمارات (62)، من اهم النتائج: وجود علاقة بين جودة القرارات الإدارية ونظم المعلومات الإدارية المتمثلة في المتطلبات (مساندة واهتمام الإدارة العليا، وتنظيمية، ومادية، وبرمجية، وبشرية) وبينت مستوى متوسط للمتطلبات (المادية – والبرمجية)، ومستوى مرتفع في باقي المتطلبات، كما بينت عدم وجود إثر ذو دلاله إحصائية بين المتطلبات (المادية – البرمجية) وبين جودة القرارات الإدارية، وجود إثر ذو دلاله إحصائية في باقي المتطلبات، وبينت وجد فروق ذات دلاله إحصائية بين متغير الجنس، ونظم المعلومات الإدارية، وكذلك الجنس وجودة القرارات الإدارية، كما تبين عدم وجد فروق ذات دلاله إحصائية في باقي المتغيرات. وأوصت الدراسة بتوفير المتطلبات المادية والبرمجية، وأن تتناسب مؤهلات الموظفين مع طبيعة الأعمال الموكلة لهم، وان يكون هناك تكامل وترابط بين القرارات وتصنيف البدائل. Abstract: The study aimed to identify the role of management information systems in the quality of administrative decisions in public higher institutes in Ajdabiya city, where the descriptive and analytical approach was used, and the questionnaire was used as a tool for data collection, as well as the use of a comprehensive community survey method, and the number of forms was (62), among the most important results: There is a relationship between the quality of administrative decisions and management information systems represented in the requirements (support and interest of the top management, organizational, material, programmatic, and human) and it showed an average level of (physical - and programmatic) requirements, and a high level in the rest of the requirements, as well as the absence of a statistically significant effect between the requirements (physical - programmatic) and the quality of administrative decisions, there is a statistically significant effect on the rest of the requirements, and it showed that there were statistically significant differences between the variable of sex, management information systems, as well as gender and the quality of administrative decisions, as it was found that there were no statistically significant differences in the rest of the variables. The study recommended providing the material and program requirements, and that the qualifications of the employees match the nature of the work assigned to them, and that there be integration and interconnection between the decisions and the classification of alternatives.